The Joker the clown prince of crime - O'Neil, Dennis 1939-2020; Maggin, Elliot S. 1950-; Pasko, Martin (DC Comics, 2013)
"In these solo adventures from 1975-1976, The Joker battles villains including Two-Face, Lex Luthor, the Scarecrow and Catwoman, as well as heroes The Creeper and Green Arrow. These stories have never been collected before, and include an appearance by Sherlock Holmes. Collects THE JOKER #1-9"..